Associated Factors of Type 2 Diabetes Mellitus in Indonesian Women - Puji Amalliyah; Martalena Br Purba; Abdul Wahab; Rotua Lenawati Tindaon (Journal of Nutrition Science, 2025)
Diabetes Mellitus (DM) is a degenerative disease whose prevalence has consistently increased over the past two decades, as reported by the IDF (2017). Its etiology is complex, and it is known that the prevalence of DM is higher in women than in men in Indonesia. This study aimed to analyze the factors associated with the incidence of DM, specifically Type 2 DM, among women in Indonesia. This research employed a cross-sectional design, utilizing secondary data from the 2018 Indonesia Basic Health Research, namely Riskesdas. The study subjects were women aged 19-59 years. Bivariate data analysis was conducted using the chi-square test. The results showed that central obesity, age, physical activity, emotional mental health, and fruit and vegetable consumption are significantly associated with the occurrence of Type 2 DM in Indonesian women (p-value < 0.05). Women with central obesity had a 2.29 times higher likelihood of developing Type 2 DM compared to those without central obesity (OR = 2.29; 95% CI: 2.09–2.50). Elevated odds were also observed in pre-elderly women aged 45-59 years (OR = 24.33; 95% CI: 15.86–37.34), those with insufficient physical activity (OR = 1.15; 95% CI: 1.03–1.28), those experiencing emotional mental health disorders (OR = 1.65; 95% CI: 1.45–1.88), and those with inadequate fruit and vegetable consumption (OR = 0.77; 95% CI: 0.67–0.89).